Neotectônica da bacia do araripe próximo a zona de cisalhamento patos e no vale do araripe: insights a partir da geomorfometria - Oliveira, Viktor Ferreira de (2024)
This study examines the tectonic activity in the northern segment of the Araripe Basin, located in southern Ceará state, NE Brazil, near the Patos shear zone, using morphometric indexes derived from SRTM imagery. The research integrates various morphometric parameters, including the Stream Length Gradient (SL), Asymmetry Factor (AF), Mountain-front Sinuosity (SMF), and Hypsometric Integral (HI), to develop a Composite Index of Tectonic Activity (CIT), which is further refined into the Relative Tectonic Activity Index (IAT), which indicates the degree of influence of tectonic activity on a given area. This approach facilitates a comprehensive assessment of tectonic processes and landscape evolution. The findings indicate that 26.75% of the studied region demonstrates a high IAT value, while 3.34% is categorized as very high. The majority of the area, encompassing 59.93%, shows moderate tectonic activity. Through a combined analysis of these indexes and morphological analyses, which highlight the impact of horsts and grabens on the terrain, the study identifies areas most influenced by tectonic activity in shaping the landscape